THE DARK SIDE OF GLP-1 ANALOGS: ADVERSE EFFECTS, LIMITATIONS, AND SAFETY CONCERNS - Dudzińska, Katarzyna; Kaftan, Adam; Plenikowski, Jan; Kahsin, Aleksander; Kacprzak , Sandra; Greluk , Aleksandra; Żuk , Jonasz; Ciszewski , Wojciech; Jurewicz , Alicja; Plenikowska , Zofia (International Journal of Innovative Technologies in Social Science, 2026)
The aim of this work is to comprehensively review and highlight the adverse effects, clinical limitations, and safety concerns associated with the use of GLP-1 receptor agonists (GLP-1 RAs), with particular emphasis on the digestive, endocrine, and cardiovascular systems, as well as the risks of off-label misuse. A comprehensive literature review was conducted using the PubMed database and Polish Summaries of Product Characteristics (SmPC). While GLP-1 analogs provide significant metabolic benefits, they carry substantial risks, including gastrointestinal distress (nausea, vomiting, delayed gastric emptying), potential skeletal muscle loss, and psychiatric effects such as suicidal ideation.The use of GLP-1 receptor agonists demonstrates significant hepatoprotective potential, manifested by a beneficial modulation of biochemical liver markers in patients with fatty liver disease. Analysis of the impact on other systems shows that while these drugs are cardioprotective, they may cause a modest increase in resting heart rate. Regarding body composition, GLP-1 RAs lead to a reduction in fat-free mass, which accounts for less than 20% of total weight loss, although this poses a risk of sarcopenia in older populations. To mitigate this, pharmacotherapy should be integrated with resistance training and high protein intake. The growing trend of off-label misuse for cosmetic weight loss further exacerbates safety concerns. Optimizing therapy requires an integrated approach and careful patient monitoring to balance metabolic gains with musculoskeletal and psychological stability.